1985
DOI: 10.1111/j.1476-5381.1985.tb08884.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of stimulatory actions of cadmium ion on the mouse diaphragm

Abstract: 3 ( + )-Tubocurarine and P-bungarotoxin had no effect on Cd2+-induced spontaneous contractions indicating that they may be myogenic rather than neurogenic in origin. 4 By use of conventional microelectrodes, it was found that Cd2+ not only depolarized the muscle membrane but also induced spontaneous action potentials at a high frequency (173 ± 17 Hz). 5 It is concluded that increased Na+ permeability of the muscle membrane is the essential step bringing about spontaneous contractions. The binding of Cd2+ to -S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…By the use of conventional microelectrodes, it was found that Cd +2 not only depolarized the muscle membrane, but also induced spontaneous action potentials at a high frequency (Fu and Lin-Shiau 1985). It was reported that increased Na + permeability of the muscle membrane was the essential step bringing about spontaneous contractions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By the use of conventional microelectrodes, it was found that Cd +2 not only depolarized the muscle membrane, but also induced spontaneous action potentials at a high frequency (Fu and Lin-Shiau 1985). It was reported that increased Na + permeability of the muscle membrane was the essential step bringing about spontaneous contractions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the phrenic nerve-diaphragm preparation of the mouse showed that Cd +2 increased the contractions (Fu and Lin-Shiau 1985). By the use of conventional microelectrodes, it was found that Cd +2 not only depolarized the muscle membrane, but also induced spontaneous action potentials at a high frequency (Fu and Lin-Shiau 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation